2016
DOI: 10.1111/myc.12501
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis outbreak among paediatric refugee population, an evolving healthcare challenge

Abstract: Outbreaks of tinea capitis (TC) represent a major medical and economic burden. Population migrations have become a phenomenon of increasing relevance for medical conditions management. Given the recent massive arrival of immigrants, we sought to determine epidemiologic trends for TC among paediatric populations at the Tel Aviv Medical Center. We conducted a retrospective study of all TC cases diagnosed between 2010 and 2014 in a paediatric dermatology unit of a tertiary medical centre, serving as a referral ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
1
36
0
2
Order By: Relevance
“…In recent decades, an increase in TC due to African species of dermatophytes has been reported from cosmopolitan centers in Europe and the Middle East (Table ) . In the Montreal area over the past 17 years, although the overall number of TC cases did not change significantly (mean 344 per year), there was a sixfold increase in African species of dermatophyte infections in children mainly due to anthropophilic M. audouinii and T. soudanense (from 6/82 [7%] in 2000 to 37/95 [39%] in 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, an increase in TC due to African species of dermatophytes has been reported from cosmopolitan centers in Europe and the Middle East (Table ) . In the Montreal area over the past 17 years, although the overall number of TC cases did not change significantly (mean 344 per year), there was a sixfold increase in African species of dermatophyte infections in children mainly due to anthropophilic M. audouinii and T. soudanense (from 6/82 [7%] in 2000 to 37/95 [39%] in 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, Microsporum canis has been reported to be the predominant organism causing TC in Israel . The recent TC outbreak in the Tel Aviv area among children of refugees from Eastern Africa had led to the emergence of novel TC‐associated predominant pathogens, including prevalence Trichophyton violaceum, Trichophyton soudanense and Microsporum audouinii …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a TC outbreak in the Tel Aviv area among children of refugees who have fled from combat zones in Eastern Africa. This resulted in a shift of the causative pathogen of TC in Israel from Microsporum canis that was more common prior to this outbreak to Trichophyton violaceum and Microsporum audouinii …”
Section: Introductionmentioning
confidence: 99%
“…A retrospective review of paediatric refugees from East Africa at a tertiary care centre in Tel Aviv revealed high rates of tinea capitis over the 4-year study period 26. The authors noted differences in the causative organisms compared with Israeli-born children and postulated that the outbreaks were related to poor living conditions and crowded residences.…”
Section: Global Health Problem Analysismentioning
confidence: 99%